Deformation mechanisms in a metastable beta titanium twinning induced plasticity alloy with high yield strength and high strain hardening rate. (15th June 2018) - Gao, Junheng; Huang, Yuhe; Guan, Dikai; Knowles, Alexander J.; Ma, Le; Dye, David; Rainforth, W. Mark
Abstract: Metastable β titanium alloys with both twinning (TWIP) and martensite transformation (TRIP) usually exhibit a low yield strength of between 200 and 500 MPa, but high strain hardening rate and large uniform elongation. Alloys that exhibit twinning on a single system provide a higher yield strength, but a lower strain hardening rate. Here, for the first time, we report a new alloy (Ti-7Mo-3Cr wt%) with both high yield strength (695 MPa) and high work hardening rate (∼1900 MPa) and a substantial 33.3% uniform elongation. The deformation mechanisms were systematically investigated using EBSD and TEM for samples strained to 1.3%, 5% and 16%. The high yield strength was achieved through initial deformation mechanisms of two twin systems, namely both 332<113> and 112<111> twinning. Importantly, the martensite transformation was suppressed at this stage of deformation. The combination of two twin systems, with approximately the same intensity, resulted in a high strain hardening rate (1600 MPa–1900 MPa), much greater compared to alloys that exhibit a single twin system. Moreover, the TRIP effect was observed at strains greater than 5%, which also contributed to the high strain hardening rate large uniform elongation. Graphical abstract: Schematic illustration of the microstructural evolution of a metastable β titanium twinning induced plasticity alloy with an increase of strain. The activation of different deformation mechanisms is shown from annealing state to the strain (16%) around the highest strain hardening rate. Image 1